Likert's Profiles of Organizational Characteristics (POC) questionnaire application to three institutions - Rusgal, Milandre Bugarin 1939-
The perceptions of 20 deans and 105 tenured faculty members on the type of management characteristics dominantly practised in their institutions, were analyzed using Fisher's t-values, split-half reliability coefficient, and Pearson Product Moment Correlation. Administrator and faculty perceptions differed significantly in eight environmental dimensions (leadership, motivation, communication, interaction influence, decision making, goal setting and ordering, control and review, and performance goals and training processes) with administrators consistently scoring high in all dimensions. The administrators differed significantly in their perceptions of all the dimensions except interaction influence and decision making. Faculty respondents differed significantly in their perceptions of all eight dimensions. The three institutions exhibit distinct management styles.